PROTOTYPE SISTEM MONITORING DAN PEMBERI PAKAN IKAN HIAS BERBASIS WEMOS D1 MINI DENGAN KENDALI TELEGRAM - Haris Chaerisma (CV. Multi Kreasi Media, 2023)
Keeping ornamental fish is a hobby that has recently become a popular activity for the community. Various activities make it difficult for ornamental fish keepers to feed ornamental fish and difficult to control the water condition of an ornamental fish aquarium. Feeding ornamental fish into the aquarium is difficult to do because of the dense activity. For this problem, a Wemos d1 mini-based tool was developed which is connected to a servo motor as a system for opening and closing fish feed containers, ultrasonic sensors as a system that detects the rest and availability of fish feed and a turbidity sensor as a system that monitors water conditions with telegram control.In this research method using the prototype method and the testing method using a test of the response of the tool and telegram, the average weight issued is 5.3gram, 10.3gram and 15.3gram, the average ultrasonic sensor in detecting the rest of the feed is 3.01 % and the turbidity sensor detects turbidity with 4 water samples (a), (b) clean water with turbidity 0 and 2, water sample (c) cloudy water with turbidity 6 and water sample (d) very cloudy water with turbidity 13.